2008
DOI: 10.1103/physrevb.77.235207
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and defect reactions between donors, C, and vacancies in Ge. I. Experimental results

Abstract: The diffusion of self-atoms and n-type dopants such as phosphorus, arsenic, and antimony in germanium was studied by means of isotopically controlled multilayer structures doped with carbon. The diffusion profiles reveal an aggregation of the dopants within the carbon-doped layers and a retarded penetration depth compared to dopant diffusion in high-purity natural Ge. Dopant aggregation and diffusion retardation are strongest for Sb and similar for P and As. In addition, the shape of the dopant profiles change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
157
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 41 publications
8
157
0
1
Order By: Relevance
“…C atoms have been observed to be relatively immobile; however, they can retard the diffusion of phosphorus ͑P͒, arsenic ͑As͒, and antimony ͑Sb͒ atoms in Ge. 26,27 Recent experimental studies by Silvestri et al 15 ͑using SIMS͒ concluded that Si diffusion in Ge is mediated by V with an activation enthalpy of 3.32 eV, whereas previous studies determined values in the range of 2.9-3.47 eV. [12][13][14] The diffusion of Si in Ge is slower than Ge self-diffusion.…”
mentioning
confidence: 94%
“…C atoms have been observed to be relatively immobile; however, they can retard the diffusion of phosphorus ͑P͒, arsenic ͑As͒, and antimony ͑Sb͒ atoms in Ge. 26,27 Recent experimental studies by Silvestri et al 15 ͑using SIMS͒ concluded that Si diffusion in Ge is mediated by V with an activation enthalpy of 3.32 eV, whereas previous studies determined values in the range of 2.9-3.47 eV. [12][13][14] The diffusion of Si in Ge is slower than Ge self-diffusion.…”
mentioning
confidence: 94%
“…The topmost near surface 100 nm thick natural Ge layer is amorphous and grown on 200 nm thick crystalline Ge. This sample structure was designed for studying the simultaneous diffusion of self-and dopant atoms, whereto the dopant of interest was implanted into the top amorphous layer 8 . Structure #2 consists of five alternating 70 Ge(100 nm)/ nat Ge(100 nm) bilayers with a top 50 nm thick natural crystalline Ge layer.…”
Section: Methodsmentioning
confidence: 99%
“…The single acceptor nature of B − s is generally accepted. Experiments on the simultaneous diffusion of n-type dopants and self-atoms demonstrate that the vacancy in Ge is doubly negatively charged even under electronically intrinsic conditions 8,9 . Investigations of the electronic properties of defects in Ge resulting from electron irradiation reveal an acceptor energy level of 0.14 eV above the valence band and two donor states with energy positions of 0.08 eV and 0.24 eV below the conduction band of Ge 42 .…”
Section: B Boron Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The latter has been associated with a vacancy-mediated diffusion mechanism, 6 as opposed to Si, wherein donors diffuse through both vacancies (V's) and interstitials. 7 Furthermore, donor passivation is known to be a problem in Ge, and it has been attributed to the formation of vacancy-donor ðV M -D N Þ complexes in a few experimental [8][9][10][11] and computational 12 studies. In a recent positron study on highly n-type Ge obtained by diffusion doping, an extensive formation of V-D N complexes was found with the common donors D 2 {As, P, Sb}.…”
mentioning
confidence: 99%